Case report: Two siblings with neuronal intranuclear inclusion disease exhibiting distinct clinicoradiological findings - Liu, Yutao; Zeng, Li; Yuan, Yanpeng; Wang, Yangyang; Chen, Kai; Chen, Yan; Bai, Jiaying; Xiao, Feng; Xu, Yuming; Yang, Jing; Tan, Song (Frontiers in Neurology, 2022)
Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disorder characterized by the presence of eosinophilic hyaline intranuclear inclusions. Owing to its widely varying clinical manifestations, NIID is frequently misdiagnosed or overlooked. However, a characteristic high-intensity corticomedullary junction signal on diffusion-weighted imaging (DWI) is often indicative of NIID. In this study, we described the case of two sisters with NIID who presented with distinct symptoms and imaging data. The younger sister showed symptoms similar to those of mitochondrial encephalopathy, with a reversible high-intensity signal from the cortex on T2 and DWI. The elder sister showed a characteristic high-signal “ribbon sign” in the corticomedullary junction on DWI. Skin biopsy confirmed that both had neuronal intranuclear inclusion. Two years later, the younger sister also developed the characteristic high-signal “ribbon sign” in the corticomedullary junction on DWI. This case study provides new insights into the complexity of NIID. The findings suggest that patients with this condition, including those belonging to the same family, may exhibit varying clinical and imaging features at different times.